PREVENTION OF CARDIO VASCULAR DISEASE THROUGH AYURVEDA - Asthana, Alok Kumar; Asthana, Monika; Sharma, Payal (Asian Journal of Pharmaceutical Research and Development, 2018)
In today's era non communicable diseases are most prevalent diseases. They are also known as chronic diseases. Cardiovascular disease (heart disease) or Hridaroga is one of them. This is a lifestyle disorder and that’s why we should always focus on a healthy lifestyle. A healthy lifestyle can reduce the risk of this lethal disease. Our various bad food habits and sedentary lifestyle are the major causes for heart disease. This article will provide all of us a brief knowledge of heart disease (hridaroga). One has correctly said “Prevention is better than cure”. So, this article will mainly focus on how we can prevent heart disease through ayurveda. Ayurveda is the best pathy to prevent lifestyle disorder. Here we will see various yoga asanas, various dietary habits, lifestyle modifications we can do to prevent the disease. Keywords: Hridaroga, hridashoola, CVD